ANALISIS KERANGKA REGULASI PELAYANAN PUBLIK BERBASIS APLIKASI DI INDONESIA: MENUJU PELAYANAN YANG BERKUALITAS - Saleha, Vila Mas Mafiana; Lodan, Karol Teovani; Dompak, Timbul (Jurnal Progress Administrasi Publik, 2025)
Application-based public services in Indonesia have experienced rapid development, but are also accompanied by challenges in the regulatory framework that is not yet comprehensive. Problems such as lack of specifications in regulations, personal data protection, and accessibility are obstacles to the delivery of quality public services. This study aims to analyze the regulatory framework for application-based public services in Indonesia and identify factors that influence service quality. This study uses a descriptive qualitative method with a literature study approach. Data were obtained from various sources of literature, laws and regulations, and official documents related to application-based public services in Indonesia. The results of the study indicate that the regulatory framework for application-based public services in Indonesia still has several weaknesses, including the lack of specific specifications in regulations, ambiguity in personal data protection, and lack of standardization and interoperability in applications. In order to realize quality application-based public services, it is necessary to improve the regulatory framework to be more comprehensive, specific, and focused on community needs. Increasing accessibility, personal data protection, standardization, and application interoperability are the keys to creating effective, efficient, and quality public services.   Keywords: Public Service; Regulation; Service Quality